2015
DOI: 10.1016/j.jhazmat.2014.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantification of norovirus capsid protein in food, water, and soil using synthetic peptides with electrospray and MALDI mass spectrometry

Abstract: Norovirus infections are one of the most prominent public health problems of microbial origin in the U.S. and other industrialized countries. Surveillance is necessary to prevent secondary infection, confirm successful cleanup after outbreaks, and track the causative agent. Quantitative mass spectrometry, based on absolute quantitation with stable-isotope labeled peptides, is a promising tool for norovirus monitoring because of its speed, sensitivity, and robustness in the face of environmental inhibitors. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…HuNoV GII.4 is recognized as a major cause of acute gastroenteritis outbreaks, and sporadic illnesses caused by HuNoV GII.4 are reported ( Hartmann et al, 2015 ). To eliminate HuNoV contamination, a potentially contaminated matrix should be disinfected properly using various methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HuNoV GII.4 is recognized as a major cause of acute gastroenteritis outbreaks, and sporadic illnesses caused by HuNoV GII.4 are reported ( Hartmann et al, 2015 ). To eliminate HuNoV contamination, a potentially contaminated matrix should be disinfected properly using various methods.…”
Section: Discussionmentioning
confidence: 99%
“…Human norovirus (HuNoV), which has characteristics such as high viral load excretion, tenacious environmental sustainability, rapid propagation, and short-term immunity, causes sporadic cases of viral gastroenteritis. Owing to its high contagiousness and rapid spread around the world, it infects humans regardless of gender or age ( Hartmann et al, 2015 ). HuNoV infection is the most common cause of acute gastroenteritis, causing approximately 680 million cases per year ( CDC, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used mass spectrometric approach for pathogen identification is matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) [ 16 , 17 , 18 , 19 ]. The success of this platform is due to the multiple in vitro protocols developed for bacteria biotyping methods, many of which have been approved by regulatory agencies such as the US Food and Drug Administration (FDA).…”
Section: Virus Detection By Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…Human noroviruses (Hu-NoVs), characterized by high infectivity among humans, short-term immunity, tenacious environmental persistence, and high viral load excretion, cause sporadic cases of nonbacterial gastroenteritis and represent the most significant etiologic agent of human epidemics, regardless of age or sex, and likely owing to their high-transmissibility across industrialized nations [ 1 ]. Moreover, the Centers for Disease Control and Prevention (CDC) reported that, annually, Hu-NoV infections cause an estimated 200,000 deaths, with more than 590,000,000 cases worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%